Assessment of Prognostic Variables of Medical Importance and their Impending Role to Develop Rheumatoid Arthritis - Sh. Khuram Salam Sehgal, Huma Sattar, Awais Altaf, Amina Javaid, Asia Hussain, Hina Allah Ditta, Arif Malik, Ayesha Zahid (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the role of different prognostic variables of medical importance having potential role in the progression of rheumatoid arthritis (RA). Study Setting: This cross sectional case control study was carried out in the Institute of Molecular Biology and Biotehnology, The University of Lahore-PakistanDuring the period of from Jan 2019 to Jan 2021 METHODOLOGY:Fifty patients of rheumatoid arthritis and fifty healthy age matched males were selected to analyse the Levels of MDA (nmol/ml), SOD (U/ml), GSH (μmol/L), CAT (U/L), IL-6 (pg/ml), TNF-α (pg/ml), MMP-9 (ng/ml) and NO (μmol/L) using ABCAM elisa kits. RESULTS: Current study observed significant rise in concentrations of MDA (p = 0.025) and significantly lower concentrations of SOD (p = 0.021), GSH (p = 0.054) and CAT (p = 0.001) in the RA patient. The mean values of IL-6, TNF-α,MMP-9 and NO were 11.59±3.29 pg/ml, 26.59±5.29 pg/ml, 91.99±14.529 ng/ml and 22.259±5.29 μmol/Lin RAsubjects’ verses 3.59±0.254 pg/ml, 13.29±3.59 pg/ml, 42.29±5.88 ng/ml and 6.58±1.59 μmol/Lin healthy controle was observed respectively. CONCLUSION: Upregulation of MDA, MMP-9 and TNF-α and downregulation of SOD, GSH and CAT portrays that antioxidants have impending role in disease (RA) development and proression as depicted from strong corelations coefficients matrix. The results of different variables in the present study shows that these markers may be used as predictive markers of prognostic importance in future to predict the disease severity and theranostic importance.